Introducing nuclei scatterer patterns into histology based intravascular ultrasound simulation framework - Kraft, Silvan; Karamalis, Athanasios; Sheet, Debdoot; Drecoll, Enken; Rummeny, Ernst J.; Navab, Nassir; Noel, Peter B.; Katouzian, Amin (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2013)
Medical ultrasonic grayscale images are formed from acoustic waves following their interactions with distributed scatterers within tissues media. For accurate simulation of acoustic wave propagation, a reliable model describing unknown parameters associated with tissues scatterers such as distribution, size and acoustic properties is essential. In this work, we introduce a novel approach defining ultrasonic scatterers by incorporating a distribution of cellular nuclei patterns in biological tissues to simulate ultrasonic response of atherosclerotic tissues in intravascular ultrasound (IVUS). For this reason, a virtual phantom is generated through manual labeling of different tissue types (fibrotic, lipidic and calcified) on histology sections. Acoustic properties of each tissue type are defined by assuming that the ultrasound signal is primarily backscattered by the nuclei of the organic cells within the intima and media of the vessel wall. This resulting virtual phantom is subsequently used to simulate ultrasonic wave propagation through the tissue medium computed using finite difference estimation. Subsequently B-mode images for a specific histological section are processed from the simulated radiofrequency (RF) data and compared with the original IVUS of the same tissue section. Real IVUS RF signals for these histological sections were obtained using a single-element mechanically rotating 40MHz transducer. Evaluation is performed by trained reviewers subjectively assessing both simulated and real B-mode IVUS images. Our simulation platform provides a high image quality with a very promising correlation to the original IVUS images. This will facilitate to better understand progression of such a chronic disease from micro-level and its integration into cardiovascular disease-specific models. © 2013 SPIE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acoustic; Finite Differences; Intravascular; Nuclei; Scatterer; Simulation; Ultrasound